2020
DOI: 10.3892/mmr.2020.10974
|View full text |Cite
|
Sign up to set email alerts
|

HER4 promotes the progression of colorectal cancer by promoting epithelial‑mesenchymal transition

Abstract: colorectal cancer (crc) remains one of the most common cancer types worldwide. a few previous studies have examined whether Her4 may promote the progression of crc. The present study examined the associations among the expression levels of members of the Her family, and investigated the potential mechanism underlying the function of Her4 in crc cells. immunohistochemistry analysis was conducted to detect the expression levels of Her family members in patients with crc. Her4 expression was knocked down using sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Several studies have investigated the molecular factors that encourage CRC progression and metastasis. Li et al (2020) and Jia et al (2020) both demonstrated that EMT is associated with metastatic ability in CRC. To date, the most effective therapy against CRC is chemotherapy combined with targeted therapy such as anti-VEGF, which inhibits pro-angiogenic factors to kill both cancer cells and their blood supplies.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have investigated the molecular factors that encourage CRC progression and metastasis. Li et al (2020) and Jia et al (2020) both demonstrated that EMT is associated with metastatic ability in CRC. To date, the most effective therapy against CRC is chemotherapy combined with targeted therapy such as anti-VEGF, which inhibits pro-angiogenic factors to kill both cancer cells and their blood supplies.…”
Section: Discussionmentioning
confidence: 97%
“…Biaocchi and colleagues investigated the expression of HER4 in 109 CRC patients with high-risk of recurrence after radical surgery and found positive membranous expression of HER4 to be an independent prognostic factor for recurrence [ 20 ]. In a more recent study, HER4 expression was found to promote the progression of colorectal cancer through epithelial-mesenchymal transition and was related to an unfavourable clinical outcome in patients with CRC [ 51 ]. Despite the membranous cellular localisation of HER4 in our study, which was around 3%, we found overall 48% of the cases were HER4 positive.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study described a tumor suppressor function for ERBB4 known as HER4 in triple-negative breast carcinoma 39 . However, another study demonstrated that ERBB4 could promote the progression of colorectal adenocarcinoma through epithelial-mesenchymal transition 40 . Although ERBB4 as a prognostic marker has been debated, the morphology of the solid type is similar to invasive ductal carcinoma of triple-negative breast carcinoma compared to colorectal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%